Otimização de nanoantenas plasmônicas para células solares orgânicas - SILVA JÚNIOR, Marcelino Lopes Corrêa da (Universidade Federal do Pará, 2017)
This work shows a theoretical nanoantennas study about organic solar cells of thin films, occasioning the increase in the efficiency of light absorption. The unitary organic solar cell formed by a reflector silver block, an active layer formed by the semiconductor P3HT:PCBM and a nanoantenna, also made of silver. The numerical analysis of the device is made through the Finite Element Method; the materials are analysed from the relative permittivity. Firstly, we executed the validation of the nanostructure through the numerical method. Then, we apply the geometric optimization process in the other nanoantenna models. This optimization process was based on nanoantennas geometrical parameters preserving its superficial area. Since were considered four new models of nanoantennas with different geometrical parameters, which means, conical nanoantennas, root cone, and exponential root cone 1 and 2. It was observed, from the efficiency of integrated absorption for different incidence angles and light polarization, current density and plasmonic decay that the nanoantennas, the root cone and the exponential cone 2, gave better performance compared to the other models.